Selenium Kinetics in Humans Change Following 2 Years of Supplementation With Selenomethionine - Patterson, Blossom H.; Combs, Gerald F.; Taylor, Philip R.; Patterson, Kristine Y.; Moler, James E.; Wastney, Meryl E. (Frontiers in Endocrinology, 2021)
Background. Increased selenium (Se) intake may improve health and reduce cancer incidence. Objective. To determine which pools and pathways of Se metabolism in vivo change in response to Se-supplementation. Methods. We compared Se kinetics in humans (n=31, aged 40±3 y (mean ± SEM) studied twice after oral tracer administration; initially (PK1), then after supplementation for 2 y with 200 µg/d of Se as selenomethionine (SeMet) (PK2). On each occasion, we administered 2 stable isotope tracers of Se orally: SeMet, the predominant food form, and selenite (Na276SeO3, or Sel), an inorganic form. Plasma and RBC were sampled for 4 mo; urine and feces were collected for the initial 12 d of each period. Samples were analyzed for tracers and total Se by isotope dilution GC-MS. Data were analyzed using a compartmental model, we published previously, to estimate fractional transfer between pools and pool masses in PK2. Results. We report that fractional absorption of SeMet or Sel do not change with SeMet supplementation and the amount of Se absorbed increased. The amount of Se excreted in urine increases but does not account for all the Se absorbed. As a result, there is a net incorporation of SeMet into various body pools. Nine of the 11 plasma pools doubled in PK2; 2 did not change. Differences in metabolism were observed for SeMet and Sel; RBC uptake increased 247% for SeMet, urinary excretion increased from 2 plasma pools for Sel and from 2 different pools for SeMet, and recycling to liver/tissues increased from one plasma pool for Sel and from 2 others for SeMet. One plasma pool increased more in males than females in PK2. Conclusions. Of eleven Se pools identified kinetically in human plasma, two did not increase in size after SeMet supplementation. These pools may be regulated and important during low Se intake.